Common Ownership and Corporate Social Responsibility - Dai, Xin; Qiu, Yue (The Review of Corporate Finance Studies, 2021)
Abstract This paper studies the effect of common ownership on corporate social responsibility (CSR). We find that common ownership is positively associated with a firm’s CSR score. The effect is stronger for firms in more competitive industries. We propose a two-stage duopoly game in which CSR serves as a commitment device to expand output aggressively to understand the empirical results. (JEL G30, D21, D22, L13, L21, L22) Received December 10, 2019; editorial decision September 9, 2020 by Editor: Gregor Matvos. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.